‘As if it was something spoken by a friend’: Digital vote-canvassing networks on Facebook during the 2013 Bangkok Gubernatorial Election Campaign - Pratheepwatanawong, Mukda (Center for Southeast Asian Social Studies (CESASS), 2018)
Vote-canvassers are a central part of Thai elections and this role has been integrated into the digital age. The relationships among the election candidates, vote-canvassers and voters are fundamental in managing the network of communication during election campaigns. Adapting the idea of the traditional vote-canvassing network for the analysis of electoral politics in the digital arena and using the concept of two-steps flow, this paper explores the way in which Facebook was used to establish and develop ?digital vote-canvassing networks? during the 2013 Bangkok gubernatorial election campaign, with the use of multimodal analysis and interviews election candidates and their public relations personnel for data collection. This paper argues that vote-canvassing systems become ?digital? when a candidate?s public relations personnel acted as core vote-canvassers to manage and transmit campaign messages on the candidate?s Facebook page on behalf of the candidate, while the candidate?s followers interacted and spread the candidate?s campaign message to their own networks, enabling more SNSs users to be exposed to the campaign content. The mediation of election campaign is no longer only dominated by candidates or political parties, but public relations personnel who demonstrated their value and skills in managing as well as personalising the dissemination and interaction of messages that candidates aimed to communicate to their followers. The development of relationships among people connected to the digital vote-canvassing networks was integrated through the coordination and dissemination of campaign content on Facebook to enhance the electoral ties between candidates and voters. Thus, the spreading of content on Facebook in part mirrors the traditional ?vote-canvassing system? in terms of the importance of networks. Both the networks of SNSs and traditional ?vote-canvassing system? involve the idea of network expansion, influential communication and development of relationships between people connected on the network. The core idea of digital vote-canvassing networks is to make campaign messages on SNSs reach as many SNS users as possible.